Gambaran Kejadian Burnout Perawat Pelaksana di Ruang Rawat Inap Rumah Sakit Umum Daerah Dokter Soedarso Pontianak - Juniarsi, Tya; Bhakti, Wida Kuswida; Sutrisno, Sutrisno; Wahyuni, Tri; Ariyanti, Sri (Indra Institute Research & Publication, 2023)
Burnout is a collection of symptoms that arise due to the use of energy exceeding one's resources resulting in the appearance of physical, emotional and mental exhaustion. Context about burnout appears in public services such as nurses, social workers, service companies, the education sector, and others related to services that involve interpersonal relationships which cause the appearance of the three signs burnout. Experienced nurse burnout will tend to be cynical towards other people and patients, feel tired all day long, feel unable to do work and even start to be reluctant to work. In severe conditions there will be a desire to stop working. If the nurse experiences burnout , of course, will hinder performance and be inconsistent with the vision and mission of the hospital in improving the quality of nursing services. Burnout It has a huge impact on the human immune system. Excessive stress will have an impact on increasing hormones cortisol which can cause prolonged stress, even lead to depression. Purpose : Obtain in-depth information about the description of the incident burnout executive nurse in the inpatient room of the Dokter Soedarso Pontianak Regional General Hospital. Research methods : This type of research is descriptive quantitative. Sampling technique using engineering purposive sampling and proportional stratified random sampling with the number of respondents as many as 155 people spread across 13 inpatient rooms. The data analysis used was univariate and bivariate using the correlation test Spearman's rho. Research result : there were 76 respondents (49%) experienced burnout low category, 56 respondents (36.1%) experienced burnout moderate category, and 23 respondents (14.8%) experienced burnout high category. There is a relationship between age and level burnout ( p-value = 0.032), there is a relationship between gender and level burnout ( p-value = 0.005), there is no relationship between education level and level burnout ( p-value = 0.224), and there is no relationship between length of service and level burnout ( p-value = 0.099). Conclusion : as a whole the implementing nurses in the inpatient room of the Dokter Soedarso Pontianak Hospital experienced burnout , more than 50% of them are in the medium and high categories. Of the four variable characteristics of the respondents, which have a significant relationship with the level burnout are age and gender.